Kajian Arsitektur Islam dan Persepsi Keestetikan Masjid di Kota Kendari - Reksa Israjab; Firmansyah Firmansyah; La Pande Jurumai (Jurnal Inovasi Sains dan Teknologi (INSTEK), 2023)
The priority in building a mosque is very important because as a place of worship for Muslims, there are still many mosques that do not apply the principles of Islamic architecture both in terms of the application of the interior and exterior of the building. - Rules of the Qur'an and Hadith The research method of this journal uses a qualitative research method by collecting observational data, namely observing and recording signs that occur in a location. Analysis of a matter in the application of the rules of the 10 mosques observed that there are three mosques that are not appropriate accordance with the rules of Islamic architecture. The results of observations of mosques in the city of Kendari have a shape and appearance that tend to use tiered roofs with the addition of stainless cubes as an architectural feature. Observations show that the mosque has a relatively long building age but its shape changes are still maintained.